Are Changes in Personality Traits and Alcohol Use Associated? A Cohort Study Among Young Swiss Men - Gmel, Gerhard; Marmet, Simon; Studer, Joseph; Wicki, Matthias (Frontiers in Psychiatry, 2020)
Objective It is well known that certain personality traits are associated with alcohol use. Because less is known about it, we wished to investigate whether changes in alcohol use were longitudinally associated with changes in personality and in which direction the influence or causation might flow. Methods Data came from the self-reported questionnaire answers of 5125 young men at two time points during the Cohort study on Substance Use Risk Factors (C-SURF). Their average ages were 20.0 and 25.4 years old at the first and second wave assessments, respectively. Four personality traits were measured: a) aggression–hostility; b) sociability; c) neuroticism–anxiety; and d) sensation seeking. Alcohol use was measured by volume (drinks per week) and binge drinking (about 60+ grams per occasion). Cross-lagged panel models and two-wave latent change score models were used. Results Aggression–hostility, sensation seeking, and sociability were significantly and positively cross-sectionally associated with both alcohol use variables. Drinking volume and these three personality traits bidirectionally predicted each other. Binge drinking was bidirectionally associated with sensation-seeking only, whereas aggression–hostility and sociability only predicted binge drinking, but not vice versa. Changes in alcohol use were significantly positively associated with changes in aggression–hostility, sensation seeking, and sociability. Associations reached small Cohen’s effect sizes for sociability and sensation seeking, but not for aggression–hostility. Associations with neuroticism–anxiety were mostly non-significant. Conclusion The direction of effects confirmed findings from other studies, and the association between changes in personality and alcohol use support the idea that prevention programs should simultaneously target both.